Sex differences in quadriceps and inspiratory muscle fatigability following high-intensity cycling - Beltrami, F. G.; Schaer, C. E.; Spengler, C. M. (Journal of Science and Medicine in Sport, 2023)
Objectives: As females have been hypothesized to have more fatigue resistant inspiratory muscles, this study aimed to compare the development of inspiratory and leg muscle fatigue between males and females following high-intensity cycling. Design: Cross-sectional comparison. Methods: 17 healthy young males (27±6years, VO2peak 55±10mlmin-1kg-1) and females (25±4years, VO2peak 45±7mlmin-1kg-1) cycled until exhaustion at 90% of the peak power output achieved during an incremental test. Changes in quadriceps and inspiratory muscle function were assessed via maximal voluntary contractions (MVC) and assessments of contractility via electrical stimulation of the femoral nerve and cervical magnetic stimulation of the phrenic nerves. Results: Time to exhaustion was similar between sexes (p=0.270, 95% CI -2.4 - 0.7min). MVC of the quadriceps was lower after cycling for males (83.9±11.5% vs. 94.0±12.0% of baseline for females, p=0.018). Reductions in twitch forces were not different between sexes for the quadriceps (p=0.314, 95% CI -5.5 - 16.6 percent-points) or inspiratory muscles (p=0.312, 95% CI -4.0 - 2.3 percent-points). Changes in inspiratory muscle twitches were unrelated to the different measures of quadriceps fatigue. Conclusion: Females incur similar peripheral fatigue in the quadriceps and inspiratory muscles compared with men following high-intensity cycling, despite smaller reduction in voluntary force. This small difference alone does not seem sufficient to warrant different training strategies to be recommended for women.